Cost-effectiveness analysis of nab-paclitaxel plus gemcitabine versus folfirinox in the treatment of metastatic pancreatic cancer in china. (4th July 2021) - Cui, Jiujie; Zhang, Xiaochen; Qu, Shuli; Wang, Liwei
ABSTRACT: Objectives: Nab-paclitaxel (Abraxane®) plus gemcitabine (AG) and Fluorouracil, leucovorin, irinotecan, oxaliplatin (FOLFIRINOX) have shown significant clinical benefit and been widely used as 1 st -line treatment of metastatic pancreatic cancer (mPC) in China. This study aims to compare the cost-effectiveness of AG versus FOLFIRINOX regimen for the treatment of mPC patients in China. Methods: Markov model was developed with a lifetime survival projection in Microsoft Excel® to simulate the progression of the mPC over time. The quality-adjusted life years (QALYs), resource consumption in the health care sector and incremental cost-effectiveness ratios (ICERs) were reported. Uncertainty was assessed by one-way and probabilistic sensitivity analyses. Results: AG regimen provided an effectiveness of 1.35 QALY at an average cost of USD 22, 300 whereas FOLFIRINOX regimen brought 0.82 QALY at a cost of USD 22, 980 in lifetime horizon. Therefore, AG regimen was dominant with an ICER of USD −1300 compared with FOLFIRINOX regimen. AG arm generated less drug cost, medical cost, hospitalization cost, and end-of-life cost than FOLFIRINOX arm did. Sensitivity analyses confirmed the robustness of base case findings. Conclusions: AG is likely a cost-effective option for the 1 st -line mPC treatment compared with FOLFIRINOX in China from the perspective of healthcare system.